KARAKTERISTIK KORIDOR JALAN DITINJAU DARI FISIK RUANG Studi Kasus : Koridor Jalan MT Haryono Kota Kendari - Fikrani Fadhilla Asha; Agus Rochani (Jurnal Planologi, 2017)
ABSTRACTUrban economic growth is gradually change the land use from the residential into commercial. This kind of development character could decrease the quality of the physical space and its impact that the cities were losing its’ character. Shop-lined along the road is not good in terms of the aesthetics of the city. These symptoms appear during the difficult of road users to identify their location. The elements in the corridors look physically diverse, random and not unique to easily recognizable because of those problems the need for the study of the physical characteristics of the corridor space Jl. MT Haryono is had to be done which is one of the commercial corridor in Kendari so that it can be seen should be noticed in order to accommodate changes.The method that used in this study is a qualitative method that aims to make a systematic description or picture of the physical characteristics of the corridor space Jl. MT Haryono, stock of knowledge that is presented in the study of the theory does not become limiting the study but is used as an opening insight to recognize the object of research. The analysis technique used is the visual analysis, and descriptive empirical. While the discussion is done by using several approaches. The output generated is the physical characteristics of the corridor space Jl. MT Haryono as seen from the path element, enclosure space, architectural pattern and street trees surrounding the corridor. The research results are influenced by the characteristics of the corridor function ± 80% of commercial buildings including the type of large commercial building plots with a single function or mix-used, and the type of commercial building single row. Commercial buildings represent the value of local distinctiveness and uniqueness in social and economic activities are shown through the decomposing of  the southeast Sulawesi’s custom house.Keywords: Characteristics,Corridor